Analisis Peningkatan Literasi Membaca Melalui Pendekatan Teaching at the Right Level (TaRL) Pada Siswa Kelas III Sekolah Dasar - Nanang Diana; Nurmuslimah Nurmuslimah; Hadijah Hadijah (Bima Journal of Elementary Education, 2024)
This study aims to analyze the TaRL approach in improving reading literacy among third-grade students at SDN Inpres 2 Woro. The research employs a qualitative approach with a case study design, involving 9 third-grade students. Data were collected through reading ability tests (pretest and posttest), observations, interviews, and document analysis. The results indicate that the TaRL approach is effective in enhancing students' reading abilities. In the initial assessment, 22.2% of students were at the beginner level, 33.3% were at the word level, and 44.5% were at the story level. After implementing the approach for three months, the posttest results showed no students remained at the beginner level, with improvements at the letter level (22.2%), sentence/paragraph level (22.2%), and reading quality at the story level (44.5%). Teachers noted that students became more active, motivated, and confident in reading activities. The study concludes that the TaRL approach is an effective method for improving reading literacy among elementary school students. This approach is recommended for implementation in other schools, with adjustments made according to the specific needs and learning conditions of each institution.